One new species of the genus Strobilanthes Blume (Acanthaceae ) for the flora of Vietnam - Xuyen, Do Thi; Hai, Do Van (Academia Journal of Biology, 2014)
Strobilanthes longespicatus Hayata (Acanthaceae) is a new record for the flora of Vietnam. It has some especial characters as shrub or undershrub; stems subquadrangular toward tip, glabrous; leaves oblong or oblong-lanceolate, 10-30 cm long, 3-9 cm wide; lateral veins 8-10 per side; petioles 2-4 cm long; flowers opposite in spikes, often branched at or near the base to form a loose panicle; bracteoles and calyx ciliate, rare glabrous; corolla pale purple or white, 5 subequal lobed; filaments up to 8 mm long, hirsute at base; style to 3,2 cm long, densely hirsute. It closes to S. cusia (Ness.) Kuntze but only differs as lateral veins 8-10 per side; bracts lanceolate; calyx segments equal; corolla pale purple or white. The specimens were collected in the Thainguyen province (Daitu district), Vietnam by Le Dong Tan et al.